Aggression against Nursing Personnel during the First Wave of COVID-19 Pandemic: An Internet-Based Survey - Juan Pablo Sánchez-de la Cruz; Alma Delia Genis-Mendoza; María Lilia López-Narváez; Thelma Beatriz González-Castro; Isela Esther Juárez-Rojop; Carlos Alfonso Tovilla-Zárate; Humberto Nicolini (MDPI AG, 2023)
(1) Background: health care workers, particularly nurses, have been regularly assaulted during the COVID-19 pandemic. Purpose: to evaluate the prevalence and location of assaults against nursing personnel in Latin America, and to determine predictor factors for aggression against nurses. (2) Methods: A cross-sectional online survey was answered by 374 nurses working in health care during the COVID-19 pandemic. The aggression against nurses was estimated using the Victimization Scale. (3) Results: A total of 288 nurses were included in this study. The victimization scale showed that 52.1% of nurses have suffered aggression by the general population during the COVID-19 pandemic. Males were more likely to be attacked than females (p < 0.05). Additionally, males were attacked more frequently on public transport (x2 = 6.72, p = 0.01). The home neighborhood and markets were other locations with a higher risk of being assaulted (OR: 3.39, CI: 1.53-7.50). (4) Conclusions: Our results indicate that nurses in Latin America who work during the COVID-19 pandemic and social isolation have been frequently assaulted by the general public. Males are more frequently attacked than females and the main places of aggression are public transportation, their home neighborhood and supermarkets. Implications for nursing practice: it is necessary to create and implement protocols and guidelines to support nursing personnel during the COVID-19 pandemic. This study was retrospectively registered at the Juarez Autonomous University of Tabasco (103/CIPDACS/2020) on the (08/2020).